Assessing the Empowerment of Muslim Women in Malawi: A Case Study of the Muslim Women’s Organization - Ulemu Chidyaonga Maseko (International Journal of Humanities and Social Sciences, 2025)
This study critically examines the empowerment of Muslim women in Malawi, focusing on the Muslim Women’s Organization (MWO) and its impact on gender equality within Islamic communities. It explores MWO's interpretation of Islamic women's rights, the stereotypes Muslim women face, and the factors limiting their rights. Utilizing qualitative methods, including interviews, focus groups, and participant observations, the research adopts phenomenological and feminist frameworks. Findings indicate that since its establishment in 1985, MWO has significantly advocated for gender equality by leveraging Islamic teachings and policy to support women’s empowerment, enabling Muslim women to participate in social change. However, entrenched cultural traditions, patriarchal structures, and systemic poverty remain barriers to empowerment
Assessing the Empowerment of Muslim Women in Malawi: A Case Study of the Muslim Women’s Organization explores how faith, culture, and activism intersect to shape the lives of Muslim women in Malawi. Through the lens of Islamic feminism and the work of the Muslim Women Organization (MWO), the book challenges stereotypes, highlights grassroots advocacy, and presents faith-driven strategies for gender equality. It is a bold and timely contribution to the discourse on women’s empowerment in conservative religious settings.
Keywords: women; INTERDISCIPLINARY RESEARCH AREAS::Gender studies; gender; Islam; HUMANITIES and RELIGION::Religion/Theology; HUMANITIES and RELIGION; africa